Dead-space corrected GaInP/GaAs composite collector double heterojunction bipolar transistors - Poh, Z. S.; Yow, H. K.; Ong, D. S.; Houston, P. A.; Krysa, A. B. (AMER INST PHYSICS, 2007)
GaInP/GaAs/GaInP double heterojunction bipolar transistors incorporating dead-space corrected composite collectors were investigated experimentally. The optimized DHBT with a 10-nm lowly doped GaAs spacer and a 5-nm highly doped GaInP spacer has extended the operating range of the collector-emitter voltage, V(CE), by maximizing the collector-emitter voltage at the onset of the multiplication, V(CE,onset), to 20 V, while minimizing the saturation voltage, V(CE,sat) (< 1 V), and maintaining the nominal breakdown voltage, BV(CEO), of the GaInP collector at 25 V. The design incorporating an Al(0.11)Ga(0.89)As spacer rather than a GaInP spacer within the lowly doped GaAs-GaInP composite collector demonstrated similar breakdown behavior. (c) 2007 American Institute of Physics.